(untitled) (Veterinária Notícias, 2022)
Granulomatous sebaceous adenitis is characterized by a chronic idiopathic dyskeratosis, with low prevalence in canine population. This disease results from degeneration and atrophy of the sebaceous glands, and so far, no known causes have been attributed, but studies suspect genetic involvement, autoimmune response or anatomical anomalies of the gland. Sebaceous adenitis most often affects dogs’ breeds as Akita, Samoyed and Poodle, which even tend to manifest this disorder more severely. Findings include local or generalized pyoderma, alopecia, hyperkeratosis and seborrhea. The diagnosis is defined by histopathological examination, after ruling out other dermatological or systemic diseases. This paper contains the case of a canine, Akita, aged 5, diagnosed with granulomatous sebaceous adenitis and pseudocyesis. She underwent ovariosalpingohisterectomy and correction of reproductive changes, in in addition, initiated topical therapy with keratolytic shampoo, mineral oil and omega-3, showing a totally satisfactory response, after 3 months of the intervention. Currently, the patient has had clinical remission of all manifestations and is with a good quality of life.